2007
DOI: 10.1682/jrrd.2006.12.0158
|View full text |Cite
|
Sign up to set email alerts
|

Motor impairment after severe traumatic brain injury: A longitudinal multicenter study

Abstract: Abstract-Neuromotor impairment is a common sequela of severe traumatic brain injury (TBI) but has been understudied relative to neurocognitive outcomes. This multicenter cohort study describes the longitudinal course of neurological examination-based motor abnormalities after severe TBI. Subjects were enrolled from the four lead Department of Veterans Affairs and Defense and Veterans Brain Injury Center sites. The study cohort consisted of 102 consecutive patients (active duty, veteran, or military dependent) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
145
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(148 citation statements)
references
References 31 publications
(24 reference statements)
1
145
1
1
Order By: Relevance
“…The effects of TBI are by nature heterogeneous, but moderate-to-severe TBIs can result in chronic deficits in motor function [77,78]. Recovery of motor function is associated with plasticity in spared motor circuits [79][80][81], and VNS paired with rehabilitation may enhance this plasticity to support recovery.…”
Section: Preclinical Studies For Traumatic Brain Injurymentioning
confidence: 99%
“…The effects of TBI are by nature heterogeneous, but moderate-to-severe TBIs can result in chronic deficits in motor function [77,78]. Recovery of motor function is associated with plasticity in spared motor circuits [79][80][81], and VNS paired with rehabilitation may enhance this plasticity to support recovery.…”
Section: Preclinical Studies For Traumatic Brain Injurymentioning
confidence: 99%
“…[6] Within the Physical domain, balance deficits are the one of the most common and physically limiting impairments resulting from TBI. [7,8] Balance can be described as the ability to maintain an upright position by keeping the body's center of gravity over its base of support as the body performs stationary or dynamic activity. [9,10] Previous research has suggested that upon admission to inpatient rehabilitation, almost 60% of patients with TBI will demonstrate impairment on the most basic of balance activities (sitting upright) and more than 75% will demonstrate impairment in slightly challenging balance activities (rising from sit to stand).…”
mentioning
confidence: 99%
“…Common cognitive impairments include reduced intellectual function, memory, processing speed, attention and language [1], whereas physical impairments include decreased balance, impaired proprioception, and dizziness [2,3]. These physical issues often impact the ability to ambulate and contribute to emotional impairments like depression.…”
Section: Introductionmentioning
confidence: 99%
“…Postural control is often affected due to disturbances in the vestibular system or to the motor cortex [2]. In a study by Geurts et al, static and dynamic postural control was compared in a TBI cohort against healthy controls [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation